2015
DOI: 10.4081/ejh.2015.2522
|View full text |Cite
|
Sign up to set email alerts
|

Testicular expression of NGF, TrkA and p75 during seasonal spermatogenesis of the wild ground squirrel (Citellus dauricus Brandt)

Abstract: The nerve growth factor (NGF) not only has an essential effect on the nervous system, but also plays an important role in a variety of non-neuronal systems, such as the reproductive system. The aim of this study was to compare the quality and quantity in expression of NGF and its receptors (TrkA and p75) in testes of the wild ground squirrel during the breeding and nonbreeding seasons. Immunolocalization for NGF was detected mainly in Leydig cells and Sertoli cells in testes of the breeding and nonbreeding sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 49 publications
(50 reference statements)
4
7
0
Order By: Relevance
“…Besides, this also accords with Zhang et al. () findings in wild ground squirrels, which showed that the production of NGF in testes was decreased during the non‐breeding season and increased in the breeding season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, this also accords with Zhang et al. () findings in wild ground squirrels, which showed that the production of NGF in testes was decreased during the non‐breeding season and increased in the breeding season.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with Schneidgenov a et al (2011) findings that showed less sperm motility and concentration during winter season. Besides, this also accords with Zhang et al (2015) findings in wild ground squirrels, which showed that the production of NGF in testes was decreased during the non-breeding season and increased in the breeding season.…”
Section: Discussionsupporting
confidence: 90%
“… 32 , 33 Size and weight of reproductive organs were generally related to their reproductive ability. 34 The seasonality of uterine mass shown in the present study was in agreement with extensive reports in this species, 8 , 27 and the present histological results showed that the uterine gland grew bigger, including nucleus growth and gland lumen extension in the breeding season, and the gland lumen shrunk remarkably and less nuclei were observed in the non-breeding season. These findings were similar to those observations in other seasonal breeders, such as possums and dunnarts.…”
Section: Discussionsupporting
confidence: 93%
“…Several papers were aimed at illustrating the tissue organization and protein expression of still poorly described organs from various Vertebrate and Invertebrate species: [42][43][44][45][46][47][48][49][50][51][52][53][54] here, the morphological description of the microanatomical and histological features was paralleled by the detection of specific molecules responsible for the tissue functional characteristics, also as a consequence of seasonal dynamic changes. [55][56][57] The immunolabeling of marker proteins was extensively applied in studies aimed at distinguishing stem/progenitor cells or at elucidating the process of cell differentiation and morphogenesis during pre-and post-natal development in mammals, including humans, [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] with special attention to the nervous system, 65,66 sensory organs, [67][68][69] skin, 70 lung, 70,71 and the skeletal apparatus. [72][73][74][75] Also in plants, the histochemical d...…”
Section: Histochemistry Of Single Moleculesmentioning
confidence: 99%